A doping precursor and its preparation method and application

Doping Fe and Ga in the precursor stage of the lithium-ion battery by co-precipitation method solves the problem of attenuation of electrochemical cycling performance of LNMO materials under high temperature conditions, and achieving a high voltage and thermal stability of the lithium-ion battery positive electrode material, which significantly improves the cycling stability and capacity retention rate of the battery.

CN116102077BActive Publication Date: 2025-04-29GEM CO LTD +1

Patent Information

Application Number
CN202211313516.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-04-29
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the electrochemical cycling performance of LNMO materials rapidly attenuates due to Mn ion dissolution under high temperature conditions, and the dopant synergistic effect is poor, affecting the material's cycling stability and rate performance.

Method used

The co-precipitation method is used to uniformly dopate Fe and Ga in the precursor stage to build a stable spinel structure and a stable electrolyte interface. Iron doping improves structural stability and Ga doping provides a protective effect.

Benefits of technology

The high voltage stability and thermal stability of the cathode material of lithium-ion battery are achieved, with the initial specific capacity up to 120.8mAh/g, and the capacity retention rate can reach more than 91.5% after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116102077B_ABST
    Figure CN116102077B_ABST
Patent Text Reader

Abstract

The present invention provides a doping precursor and a preparation method and application thereof, the preparation method comprising the following steps: (1) mixing a nickel source and a manganese source with a solvent to obtain a solution A, mixing an iron source with a solvent to obtain a solution B, and mixing a gallium source with a solvent to obtain a solution C; (2) adding the solution A, solution B and solution C obtained in step (1) together with an alkaline solution and a complexing agent into a reaction vessel to carry out a coprecipitation reaction; (3) centrifuging the coprecipitated product obtained in step (2) to obtain the doping precursor. In the present invention, doping is carried out by coprecipitation at the precursor stage, which has the advantages of good uniformity and simple preparation. Fe has low cost and can replace the position of Ni / Mn to achieve higher electronic conductivity and improve the thermal stability of the positive electrode; the doped Ga diffuses into the surface layer of the positive electrode material, which can play a role in maintaining the stability of the internal structure, which is equivalent to the protective effect of the coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and relates to a doped precursor, a preparation method thereof, and an application thereof. Background Art

[0002] LiNi x Mn 2-x O4 (LNMO, 0 < x < 0.5) has the advantages of low price, non-toxicity, and good rate performance. Its spinel structure has a three-dimensional lithium ion diffusion channel, a super high working voltage of about 4.7V (vs. Li / Li+), a theoretical specific capacity of 146.7 mAh / g, a reversible specific capacity of about 133 mAh / g, and an energy density as high as 650 Wh / kg. However, when there is trace water in the electrolyte, during the cycling process of LNMO, Mn dissolves from LNMO into the electrolyte, especially under high temperature conditions, resulting in a rapid attenuation of the battery capacity and a decrease in the Coulomb efficiency. Under high temperature and high pressure conditions, more HF is generated by the decomposition of the electrolyte, causing more manganese ions to dissolve, leading to a rapid attenuation of the electrochemical cycling performance. In order to improve the electrochemical performance of lithium ion batteries, the LNMO cathode material is usually doped or coated.

[0003] Since the d orbitals are not fully occupied, transition metal dopants have been used to adjust the physical and chemical properties of active materials in rechargeable batteries. The transition metal dopants that have been studied so far mainly include Co 3+ 、Fe 3+ 、Cr 3+ 、Cu 2+ 、Zn 2+ 、Ti 4+ 、V 5+ 、Zr 4+ 、Nb 5+ 、Mo 6+ 、Ru 4+ 、W 5+ etc. The doping of a small amount of foreign atoms only affects the size of the LNMO lattice, but does not change the symmetry of the original structure. Different dopants can improve the high-voltage LNMO spinel from different aspects due to their different occupied positions and properties.

[0004] CN113735189A discloses a method for preparing a cobalt-free precursor with high specific surface area doped with Al and Zr, comprising the following steps: preparing a nickel-manganese metal salt solution by mixing a soluble nickel salt and a soluble manganese salt; adding a soluble zirconium salt to the nickel-manganese metal salt solution to prepare a nickel-manganese metal salt solution containing zirconium; preparing a sodium aluminate solution; adding pure water, ammonia water and liquid alkali to a reactor to prepare a base liquid, introducing nitrogen into the base liquid, starting the reactor and stirring, and simultaneously adding the nickel-manganese metal salt solution containing zirconium, sodium aluminate solution, liquid alkali and ammonia water to the reactor for reaction to obtain a precursor material; washing, filtering and drying the precursor material to obtain a cobalt-free precursor.

[0005] CN113603158A discloses a cobalt-free positive electrode material precursor, which is based on nickel manganese hydroxide, and the surface of the substrate is coated with a zirconium hydroxide layer. Its preparation method includes: preparing a mixed salt solution containing nickel, manganese and doping elements; adding pure water as a base liquid to a reactor, and then adding ammonia water; then passing nitrogen into the reactor, adding the mixed salt solution, precipitant, and ammonia water to the reactor for stirring reaction; finally, adding ZrSO4 and (NH4)2SO4 to the reactor to continue the reaction, filtering, washing, and drying after the reaction is completed to obtain a cobalt-free positive electrode material precursor.

[0006] The metal elements doped in the precursor prepared by the above scheme have poor synergy, which affects the cycle stability and rate performance of the material. Summary of the invention

[0007] The purpose of the present invention is to provide a doped precursor and a preparation method and application thereof. In the present invention, doping is performed by coprecipitation at the precursor stage, which has the advantages of good uniformity and simple preparation. Fe has low cost and can replace the position of Ni / Mn to achieve higher electronic conductivity and improve the thermal stability of the positive electrode; the doped Ga diffuses into the surface layer of the positive electrode material, which can play a role in maintaining the stability of the internal structure, which is equivalent to the protective effect of the coating layer.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a doping precursor, the preparation method comprising the following steps:

[0010] (1) mixing a nickel source and a manganese source with a solvent to obtain a solution A, mixing an iron source with a solvent to obtain a solution B, and mixing a gallium source with a solvent to obtain a solution C;

[0011] (2) adding solution A, solution B and solution C obtained in step (1) together with an alkaline solution and a complexing agent into a reaction container to carry out a coprecipitation reaction;

[0012] (3) Centrifuging the coprecipitated product obtained in step (2) to obtain the doped precursor.

[0013] In the precursor stage, the present invention uses a liquid phase multi-element uniform doping process without additional coating to construct a stable spinel structure inside the high-voltage LNMO positive electrode and achieve a chemically stable contact interface with the electrolyte. The introduction of the iron dopant leads to a more disordered structure of the cations, thereby improving the structural stability of the spinel, alleviating the CEI that is continuously formed due to the iron-rich and nickel-deficient particle surface, and increasing the Mn in the spinel. 3+ , thereby reducing the voltage polarization during cycling and improving the conductivity of the active material. 3+ During the sintering process, the electrochemically inactive Ga 3+ Ions tend to separate to the outer layer of LNMO particles, which helps to form a strong and stable interface with the electrolyte, as well as a more stable high-cation disordered spinel structure, which alleviates the thermal decomposition (i.e., oxygen release) of LNMO and the migration of transition metals from octahedral positions to tetrahedral positions during heating. Therefore, compared with the coating process, coating Ga is simpler and avoids the risk of peeling of the coating layer from the bulk material.

[0014] Preferably, the nickel source in step (1) comprises any one of nickel chloride, nickel sulfate or nickel nitrate, or a combination of at least two of them.

[0015] Preferably, the manganese source includes any one of manganese chloride, manganese sulfate or manganese nitrate, or a combination of at least two of them.

[0016] Preferably, the iron source includes any one of ferric chloride, ferric sulfate or ferric nitrate, or a combination of at least two of them.

[0017] Preferably, the gallium source includes any one of gallium chloride, gallium sulfate or gallium nitrate, or a combination of at least two of them.

[0018] Preferably, the total molar concentration of metal ions in the solution A in step (1) is 1 to 3 mol / L, for example: 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L.

[0019] Preferably, the molar concentration of the metal ions in the solution B is 0.2-1 mol / L, for example, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L or 1 mol / L.

[0020] Preferably, the molar concentration of the metal ions in the solution C is 0.15-0.5 mol / L, for example, 0.15 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L.

[0021] Preferably, the alkaline solution in step (2) comprises sodium hydroxide solution.

[0022] Preferably, the molar concentration of the alkali solution is 3-5 mol / L, for example, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L.

[0023] Preferably, the complexing agent comprises aqueous ammonia.

[0024] Preferably, the molar concentration of the ammonia water is 8 to 12 mol / L, for example, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.

[0025] Preferably, stirring is performed during the coprecipitation reaction in step (2).

[0026] Preferably, the stirring speed is 200-400 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 350 rpm or 400 rpm.

[0027] Preferably, the pH of the coprecipitation reaction is 10-11, for example, 10, 10.2, 10.5, 10.8 or 11.

[0028] Preferably, the coprecipitation reaction temperature is 40-70°C, for example, 40°C, 45°C, 50°C, 60°C or 70°C.

[0029] Preferably, the coprecipitation reaction time is 60 to 100 h, for example, 60 h, 70 h, 80 h, 90 h or 100 h.

[0030] In a second aspect, the present invention provides a doping precursor, wherein the doping precursor is prepared by the method described in the first aspect, and the chemical formula of the doping precursor is Ni x Fe y Ga z Mn 1-x-y-z (OH)2, wherein x is 0.1 to 0.3 and y is 0.1 to 0.2.

[0031] Preferably, the median particle size D50 of the doped precursor is 3 to 12 μm, for example, 3 μm, 5 μm, 8 μm, 10 μm or 12 μm.

[0032] In a third aspect, the present invention provides a positive electrode material, which is obtained by mixing the doped precursor described in the second aspect with a lithium source and then sintering the mixture.

[0033] In a fourth aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material as described in the third aspect.

[0034] In a fifth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the fourth aspect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) In the precursor stage, the present invention uses a liquid phase multi-element uniform doping process without additional coating to construct a stable spinel structure inside the high-voltage LNMO positive electrode and achieve a chemically stable contact interface with the electrolyte.

[0037] (2) The introduction of iron dopants leads to a more cation-disordered structure, which improves the structural stability of spinel, alleviates the continuous formation of CEI due to iron-rich and nickel-deficient particle surfaces, and increases the Mn 3+ , thereby reducing the voltage polarization during cycling and improving the conductivity of the active material. 3+ During the sintering process, the electrochemically inactive Ga 3+ Ions tend to separate to the outer layer of LNMO particles, which helps to form a strong and stable interface with the electrolyte, as well as a more stable high-cation disordered spinel structure, which alleviates the thermal decomposition (i.e., oxygen release) of LNMO and the migration of transition metals from octahedral positions to tetrahedral positions during heating. Therefore, compared with the coating process, coating Ga is simpler and avoids the risk of peeling of the coating layer from the bulk material.

[0038] (3) The initial specific capacity of the battery made from the doped precursor of the present invention can reach more than 120.8 mAh / g, and the capacity retention rate can reach more than 91.5% after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the SEM image of the doped precursor described in Example 1.

[0040] Figure 2 This is the SEM image of the precursor described in Comparative Example 1. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0042] Example 1

[0043] This embodiment provides a doping precursor, and the preparation method of the doping precursor is as follows:

[0044] (1) A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared according to a Ni:Mn molar ratio of 3:10, denoted as solution A, and a 0.385 mol / L iron sulfate solution was prepared, denoted as solution B, and a 0.1 mol / L gallium sulfate solution was prepared, denoted as solution C;

[0045] (2) Under nitrogen protection, solution A, solution B and solution C, a 4 mol / L sodium hydroxide solution and a 10 mol / L ammonia solution were added to the reactor at the same time, the pH of the reactor was controlled to 10.5, and the coprecipitation reaction was carried out at 50° C. and a stirring speed of 300 rpm for 80 hours;

[0046] (3) When the precursor particle size in the reactor reaches 8 μm, stop feeding; centrifuge and wash the reaction product; and dry to obtain the finished Ni 0.18 Fe 0.15 Ga 0.04 Mn 0.6 (OH)2, the SEM image of the precursor is shown in Figure 1 shown.

[0047] Example 2

[0048] This embodiment provides a doping precursor, and the preparation method of the doping precursor is as follows:

[0049] (1) A 2 mol / L mixed solution of nickel sulfate and manganese sulfate was prepared according to a Ni:Mn molar ratio of 1:3, denoted as solution A, and a 0.385 mol / L iron sulfate solution was prepared, denoted as solution B, and a 0.12 mol / L gallium sulfate solution was prepared, denoted as solution C;

[0050] (2) Under nitrogen protection, solution A, solution B and solution C, a sodium hydroxide solution with a concentration of 4.5 mol / L and an ammonia solution with a concentration of 11 mol / L were added to the reactor at the same time, the pH of the reactor was controlled to 10.6, and the coprecipitation reaction was carried out at 50° C. and a stirring speed of 300 rpm for 75 hours;

[0051] (3) When the precursor particle size in the reactor reaches 8 μm, stop feeding; centrifuge and wash the reaction product; and dry to obtain the finished Ni 0..2 Fe 0.15 Ga 0.05 Mn 0.6 (OH)2.

[0052] Example 3

[0053] The only difference between this embodiment and embodiment 1 is that the molar concentration of iron ions in the solution B is 0.1 mol / L, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0054] Example 4

[0055] The only difference between this embodiment and embodiment 1 is that the molar concentration of iron ions in solution B is 1.5 mol / L, and other conditions and parameters are exactly the same as those in embodiment 1.

[0056] Example 5

[0057] The only difference between this embodiment and embodiment 1 is that the molar concentration of gallium ions in the solution C is 0.1 mol / L, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0058] Example 6

[0059] The only difference between this embodiment and embodiment 1 is that the molar concentration of gallium ions in the solution C is 0.6 mol / L, and the other conditions and parameters are exactly the same as those in embodiment 1.

[0060] Comparative Example 1

[0061] The only difference between this comparative example and Example 1 is that no iron source and gallium source are doped, and other conditions and parameters are exactly the same as those in Example 1. The SEM image of the obtained precursor is as follows Figure 2 shown.

[0062] Comparative Example 2

[0063] The only difference between this comparative example and Example 1 is that no iron source is added, and other conditions and parameters are exactly the same as those in Example 1.

[0064] Comparative Example 3

[0065] The only difference between this comparative example and Example 1 is that no gallium source is doped, and other conditions and parameters are exactly the same as those in Example 1.

[0066] Performance Test:

[0067] The nickel-manganese precursors obtained in Examples 1-6 and Comparative Examples 1-3 were calcined with LiOH at 850°C to obtain the active material of the positive electrode material. The active material, conductive agent, and binder were mixed in a certain proportion to obtain a positive electrode slurry. The slurry was coated on aluminum foil by a coating machine and dried at low temperature. A copper foil coated with graphite was used as the negative electrode, and a certain proportion of lithium hexafluorophosphate, EC, and DMC were used as electrolytes to finally form a button-type full battery. The cycle test conditions were at 25°C to test its initial specific capacity. The battery was first activated by two cycles of charge and discharge at a current density of 0.05C, and then charged at 0.5C and discharged at 1C (1C = 250mA / g) for 100 cycles. The test results are shown in Table 1:

[0068] Table 1

[0069]

[0070]

[0071] As can be seen from Table 1, from Examples 1-2, the initial specific capacity of the battery made from the doped precursor of the present invention can reach more than 120.8 mAh / g, and the capacity retention rate can reach more than 91.5% after 100 cycles.

[0072] By comparing Example 1 with Examples 3-4, it can be seen that in the preparation process of the doped precursor of the present invention, the concentration of the iron source solution will affect the performance of the obtained precursor. When the concentration of the iron source solution is controlled at 0.2-1 mol / L, the obtained precursor has better performance. If the concentration of the iron source is too high, the CEI film formed is too thick, resulting in reduced conductivity of the precursor and weakening the performance of the battery. If the concentration of the iron source is too low, the CEI film formed is too thin and cannot effectively reduce the voltage polarization during the cycle, resulting in reduced cycle performance of the material and reduced conductivity.

[0073] By comparing Example 1 with Examples 5-6, it can be seen that in the preparation process of the doped precursor of the present invention, the concentration of the gallium source solution will affect the performance of the prepared precursor. When the concentration of the gallium source solution is controlled at 0.15-0.5 mol / L, the performance of the prepared precursor is better. If the concentration of the gallium source is too high, the interface formed between the electrode material and the electrolyte is too thick, oxygen cannot be released, and the performance of the battery is reduced. If the concentration of the gallium source is too low, the interface formed is too thin, which reduces the electrochemical performance of the material.

[0074] By comparing Example 1 and Comparative Example 1, it can be seen that the doping in the precursor stage is carried out by co-precipitation in the present invention, which has the advantages of good uniformity and simple preparation. Fe has low cost and can replace the position of Ni / Mn to achieve higher electronic conductivity and improve the thermal stability of the positive electrode; the doped Ga diffuses into the surface layer of the positive electrode material, which can play a role in maintaining the stability of the internal structure, which is equivalent to the protective effect of the coating layer.

[0075] From the comparison between Example 1 and Comparative Example 2, it can be seen that the introduction of the iron dopant leads to a more disordered structure of the cations, thereby improving the structural stability of the spinel, alleviating the continuous formation of CEI due to the iron-rich and nickel-deficient particle surface, and increasing the Mn 3+ , thereby reducing voltage polarization during cycling and improving the conductivity of the active materials.

[0076] By comparing Example 1 and Comparative Example 3, Ga 3+ During the sintering process, the electrochemically inactive Ga 3+Ions tend to separate to the outer layer of LNMO particles, which helps to form a strong and stable interface with the electrolyte, as well as a more stable high-cation disordered spinel structure, which alleviates the thermal decomposition (i.e., oxygen release) of LNMO and the migration of transition metals from octahedral positions to tetrahedral positions during heating. Therefore, compared with the coating process, coating Ga is simpler and avoids the risk of peeling of the coating layer from the bulk material.

[0077] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a doped precursor, characterized in that: The preparation method comprises the following steps: (1) mixing a nickel source and a manganese source with a solvent to obtain a solution A, mixing an iron source with a solvent to obtain a solution B, and mixing a gallium source with a solvent to obtain a solution C; (2) adding solution A, solution B and solution C obtained in step (1) together with an alkaline solution and a complexing agent into a reaction container, and carrying out a coprecipitation reaction for 60 to 100 hours at a pH of 10 to 11, a temperature of 40 to 70° C., and a stirring speed of 200 to 400 rpm; (3) centrifuging the coprecipitated product obtained in step (2) to obtain the doped precursor; The molar concentration of metal ions in the solution B is 0.2-1 mol / L; The molar concentration of metal ions in the solution C is 0.15-0.5 mol / L.

2. The preparation method according to claim 1, characterized in that The nickel source in step (1) includes any one of nickel chloride, nickel sulfate or nickel nitrate, or a combination of at least two of them.

3. The preparation method according to claim 1, characterized in that: The manganese source includes any one of manganese chloride, manganese sulfate or manganese nitrate, or a combination of at least two of them.

4. The preparation method according to claim 1, characterized in that: The iron source includes any one of ferric chloride, ferric sulfate or ferric nitrate, or a combination of at least two of them.

5. The preparation method according to claim 1, characterized in that: The gallium source includes any one of gallium chloride, gallium sulfate or gallium nitrate, or a combination of at least two of them.

6. The preparation method according to claim 1, characterized in that: The total molar concentration of metal ions in the solution A of step (1) is 1 to 3 mol / L.

7. The preparation method according to claim 1, characterized in that: The alkaline solution in step (2) comprises sodium hydroxide solution.

8. The preparation method according to claim 1, characterized in that: The molar concentration of the alkali solution is 3-5 mol / L.

9. The preparation method according to claim 1, characterized in that: The complexing agent includes aqueous ammonia.

10. The preparation method according to claim 9, characterized in that: The molar concentration of the ammonia water is 8-12 mol / L.

11. A doping precursor, characterized in that: The doped precursor is prepared by the method according to any one of claims 1 to 10, and the chemical formula of the doped precursor is Ni x Fe y Ga z Mn 1-x-y-z (OH)2, wherein x is 0.1 to 0.3 and y is 0.1 to 0.

2.

12. The doped precursor according to claim 11, characterized in that: The median particle size D50 of the doped precursor is 3 to 12 μm.

13. A positive electrode material, characterized in that: The positive electrode material is obtained by mixing the doped precursor according to claim 11 or 12 with a lithium source and then sintering the mixture.

14. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material as claimed in claim 13.

15. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 14.

Citation Information

Patent Citations

  • Cobalt-free positive electrode material precursor and preparation method thereof

    CN113603158A

  • Preparation method of Al and Zr doped cobalt-free precursor with high specific surface area

    CN113735189A

  • High-manganese solid solution as lithium ion battery anode material and preparation method thereof

    CN102956881A

Cited By

  • Doping type precursor for positive electrode lithium supplementing agent and preparation method and application thereof

    CN121627074A